An investigation into bimetallic catalysts for base free oxidation of cellobiose and glucose. Issue 9 (26th April 2017) - Cao, Yueling; Iqbal, Sarwat; Miedziak, Peter J; Jones, Daniel R; Morgan, David J; Liu, Xi; Wang, Junwei; Hutchings, Graham J
Abstract: BACKGROUND: The selective conversion of cellulose to gluconic acid under mild conditions is challenging as it has abundant intra‐and inter‐molecular hydrogen bonds that protect the β‐1, 4‐glycosidic bonds and make it intrinsically recalcitrant to depolymerize. RESULTS: Au‐Pd/TiO2 and Au‐Pt/TiO2  catalysts prepared by sol immobilization method without pre‐treatment are active and selective for the oxidation of glucose and cellobiose to gluconic acid under base‐free conditions. Important preparation parameters are the pre‐treatment of the catalyst and the metal ratio. CONCLUSION: The optimized catalyst provided a good yield of gluconic acid from cellobiose and has opened up a new catalyst system for cellobiose conversion in terms of a heterogeneous catalyst. © 2017 Society of Chemical Industry